Dosimetry and optimisation in high dose fluoroscopic and fluorographic procedures - Morrell, Rachel Elizabeth (2006)
This thesis describes the search for a practical skin dosimetry method for cardiac catheterization procedures, and the application of an optimisation strategy in barium enema imaging.